1997
DOI: 10.1021/jp970567a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Energetics of the Water/NaCl(100) Interface

Abstract: A series of correlation-corrected periodic Hartree-Fock (PHF) calculations have been performed to evaluate the structure of a single layer of water adsorbed on NaCl(100). This work was motivated by differing experimental observations which assign the water/NaCl interface structure as either a monolayer, with a single adsorbate binding site, or a 4×2 bilayer model. Quantum mechanical binding energies were computed for several adsorbate/surface geometries corresponding to 1×1 and 2×1 monolayer structures and 4×2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
(121 reference statements)
2
27
0
Order By: Relevance
“…While extensive investigations of water on the surfaces of metals, semiconductors and oxides have been carried out, 1-5 a determination of the structure of adsorbed water has been often controversial. Especially, the water/NaCl system [6][7][8][9][10][11][12][13][14][15][16][17][18] is of particular interest because of a crucial role in various areas such as environmental science and biophysics. The detailed knowledge of the adsorption structure of water on the NaCl surface would provide useful information related to the heterogeneous chemical reactions in the troposphere over oceans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While extensive investigations of water on the surfaces of metals, semiconductors and oxides have been carried out, 1-5 a determination of the structure of adsorbed water has been often controversial. Especially, the water/NaCl system [6][7][8][9][10][11][12][13][14][15][16][17][18] is of particular interest because of a crucial role in various areas such as environmental science and biophysics. The detailed knowledge of the adsorption structure of water on the NaCl surface would provide useful information related to the heterogeneous chemical reactions in the troposphere over oceans.…”
mentioning
confidence: 99%
“…The detailed knowledge of the adsorption structure of water on the NaCl surface would provide useful information related to the heterogeneous chemical reactions in the troposphere over oceans. 19,20 Despite experimental 7,8 and theoretical [9][10][11][12][13][14][15] efforts to understand adsorbed water on the NaCl(001) surface, there is a controversy on the structure of the two-dimensional (2-D) phase which is formed before the condensation of threedimensional phases. Using low energy electron differaction (LEED) analysis together with ultraviolet photoelectron spectroscopy and x-ray photoelectron spectroscopy, Fölsch et al 7 suggested a puckered quasi-hexagonal bilayer structure of c͑4 ϫ 2͒ symmetry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this technological importance, the nature of the interaction between ionic compounds and metals and ionic compounds and semiconductors raises fundamental questions [14]. Finally, it has been found that surface reactions involving atmospheric pollutants and NaCl crystallite may impact tropospheric ozone concentrations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a renewed interest in this compound, since recent studies in the field of atmospheric chemistry have linked surface reactions between NaCl and common gaseous pollutants such as HN03, N205, N02 and C10N02 to the production of ozone reducing gas-phase Cl atoms [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%